A comparative study for landslide susceptibility assessment using machine learning algorithms based on grid unit and slope unit - Deng, Niandong; Li, Yuxin; Ma, Jianquan; Shahabi, Himan; Hashim, Mazlan; de Oliveira, Gabriel; Chaeikar, Saman Shojae (Frontiers in Environmental Science, 2022)
Landslide susceptibility assessment is an important support for disaster identification and risk management. This study aims to analyze the application ability of machine learning hybrid models in different evaluation units. Three typical machine learning models, including random forest (RF), forest by penalizing attributes (FPA) and rotation forest (ROF), were merged by random subspace (RS) algorithm. Twelve evaluation factors, including elevation, slope angle, slope aspect, roughness, rainfall, lithology, distance to rivers, distance to roads, normalized difference vegetation index, topographic wetness index, plan curvature, and profile curvature, were extracted from 155 landslides in Yaozhou District, Tongchuan City, China. Six landslide susceptibility maps were generated based on the slope units divided by curvature and 30m resolution grid units. Multiple performance metrics showed that the RS-RF model based on slope units has excellent spatial prediction ability. At the same time, the method of slope unit division based on curvature is proved to be more suitable for the typical Loess tableland regions, which provides basis for the selection of evaluation units in landslide susceptibility assessment.